2013
DOI: 10.3109/13693786.2013.770607
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-3 plays an important role in protection against disseminated candidiasis

Abstract: Recent in vitro studies have implicated galectin-3 as an important receptor in host recognition and response to specific Candida species; however its role in protection against disseminated candidiasis in vivo has not been evaluated. This study investigated the importance of galectin-3 in host defense against systemic infection with the highly virulent species Candida albicans (C. albicans), and the less virulent species, Candida parapsilosis (C. parapsilosis). Mice deficient in galectin-3 (gal3−/−) were more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
57
3
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 52 publications
2
57
3
4
Order By: Relevance
“…More specifically, gal3-/-mice died significantly faster and exhibited a trend toward increased fungal burden and increased abscess formation in infected brains compared to WT mice. 186 [198,170] NLRP3 has been found critical for the control of C. albicans infections. 35 Mice deficient in NLRP3 displayed diminished serum IL-1b, reduced survival and higher fungal burdens in kidney, spleen, liver, and lung upon C. albicans infection.…”
Section: The Roles Of Prrs: Findings Using Prr-deficient Micementioning
confidence: 99%
“…More specifically, gal3-/-mice died significantly faster and exhibited a trend toward increased fungal burden and increased abscess formation in infected brains compared to WT mice. 186 [198,170] NLRP3 has been found critical for the control of C. albicans infections. 35 Mice deficient in NLRP3 displayed diminished serum IL-1b, reduced survival and higher fungal burdens in kidney, spleen, liver, and lung upon C. albicans infection.…”
Section: The Roles Of Prrs: Findings Using Prr-deficient Micementioning
confidence: 99%
“…These results are unexpected as it was reported that mice defective in galectin-3 are more sensitive to C. albicans infection. 81,82 While we do not have an explanation for this, differences could exist between both set of experiments regarding the infectious dose used and the origin of the used galectin-3 C/C and galectin-3 ¡/¡ mice (our strain is backcrossed for over 9 generations to C57BL/7 mice while this number is lower in commercial (Jackson Laboratories) mice) that could be maybe responsible for the observed discrepancies. Nevertheless, an increased resistance of galectin-3 null mice has been also observed in infections with Trypanosoma brucei, 83 Salmonella…”
mentioning
confidence: 91%
“…It is made available under a The copyright holder for this preprint (which was not . http://dx.doi.org/10.1101/080333 doi: bioRxiv preprint first posted online Oct. 12, 2016; C.Albicans infection [169].…”
Section: Cc-by-nc-ndmentioning
confidence: 99%